Facial Nerve Function After Microsurgical Resection in Vestibular Schwannoma Under Neurophysiological Monitoring - Arlt, Felix; Kasper, Johannes; Winkler, Dirk; Jähne, Katja; Fehrenbach, Michael Karl; Meixensberger, Jürgen; Sander, Caroline (Frontiers in Neurology, 2022)
Background The use of intraoperative neurophysiological monitoring, including direct nerve stimulation (especially the facial nerve), acoustic evoked potentials (AEP) and somatosensory evoked potentials (SSEP), is a helpful tool in the microsurgery of vestibular schwannoma to prevent nerve injury. Patient characteristics, and intraoperative and postoperative variables might also influence the postoperative facial nerve function. The study was performed to investigate these variables and the intraoperative neurophysiological monitoring values. Methods Seventy-nine patients with vestibular schwannoma were included consecutively into this study. Intraoperative neurophysiological monitoring, including SSEP, AEP and direct nerve stimulation for facial and trigeminal nerve electromyography, was performed utilizing digital data storage in all cases. The intensity (in volts) of the direct stimulation and the latency (in ms) for the orbicularis oculi and the orbicularis oris muscle and the amplitude (in mV) was measured. Univariate and multivariate statistical analyses concerning the different parameters was performed directly after the operation and in the subsequent follow-ups three and six months after the operation. Results The mean intensity was 0.79 V (SD 0.29). The latency and amplitude for the oris muscle was 5.2 ms (SD 2.07) and 0.68 mV (SD 0.57), respectively. The mean latency for the occuli muscle was 5.58 ms (SD 2.2) and the amplitude was 0.58 mV (SD 1.04). The univariate and multivariate statistical analyses showed significance concerning the postoperative facial nerve function and the amplitude of the direct stimulation of the facial nerve in the orbicularis oris muscle (p = 0.03). The mean diameter of the tumors was 24 mm (range 10 – 57 mm). Cross total resection and near total was achieved in 76 patients (96 %) and subtotal in three patients (4 %). The preoperative House–Brakeman score (HBS) 1 was constant in 65 (82 %) cases. The mortality in our series was 0 %; the overall morbidity was 10 %. The HBS was not influenced concerning the extent of resection. The mean follow-up was 28 months (range 6 to 60 months). Conclusion Intraoperative neurophysiological monitoring is crucial in vestibular schwannoma surgery. Repeated direct nerve stimulation and a detected decreased amplitude might show facial nerve function deterioration.